2000
DOI: 10.1007/s001470050326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Celsior and University of Wisconsin preservation solutions on hemodynamics and endothelial function after cardiac transplantation in humans: a single-center, prospective, randomized trial

Abstract: Optimal preservation of the myocardium remains a major concern in clinical and experimental heart transplantation. The present study compared the efficacy of University of Wisconsin (UW) and Celsior preservation solution with respect to myocardial performance, epicardial and microvascular endothelial vasomotor function and myocardial expression of endothelin and nitric oxide synthases in humans. Forty-one cardiac transplant recipients received either UW (n = 20) or Celsior (n = 21) preserved hearts. Catecholam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Previous studies have suggested that allografts preserved with CS have an increased post-transplant need for inotropic support. 13,14 Weaning such vasoactive support can take time and may have contributed to the longer LOS observed in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have suggested that allografts preserved with CS have an increased post-transplant need for inotropic support. 13,14 Weaning such vasoactive support can take time and may have contributed to the longer LOS observed in this study.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, the Celsior group showed less left ventricular function compared with the UW group. Some investigators reported that Celsiorpreserved hearts required more inotropic support in the early phase after transplantation [14], and these investigators assumed a reversible dysfunction as the underlying phenomenon.…”
Section: Left Ventricular Function After Preservationmentioning
confidence: 99%
“…Some investigators have shown that the Celsior solution has the advantages of being able to prevent free radical injury [10], coronary endothelial damage [11,12], and depletion of adenine nucleotides [13]. However, other investigators have reported the necessity of a higher dose of catecholamines postoperatively [14] and higher frequency of necessary defibrillations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 UW was the standard preservation solution for the investigation period, which might have contributed to the finding that increased donor serum sodium levels have no significant impact on the outcome variables assessed.…”
Section: Discussionmentioning
confidence: 79%